Seksulitas, teknologi digital, Makna Menjadi Manusia : Reflektif Filsafat Barat dan Islam - Nusqiyah Firdaus Zacrie; Nasikhin; Aang Kunaepi (Publikasi Inspirasi Indonesia, 2025)
The development of digital technology has radically changed the way humans understand sexuality and self-identity. This research aims to analyze the impact of digital technologies-such as social media, artificial intelligence, and virtual reality-on the concept of sexuality and human nature through the perspectives of Western and Islamic philosophy. Using a comparative literature study approach, this research examines the thoughts of Western philosophers (Foucault, Baudrillard) who see sexuality as a social construction and hyperreality, as well as Islamic perspectives (Al-Ghazali, Nasr) that emphasize the concepts of fitrah, nafs, and tawhid-based sexuality ethics. The results show that digital technology creates a paradox: on the one hand it liberates sexual expression, but on the other hand it blurs the boundaries between humans and machines, causing a crisis of human meaning. Islamic philosophy offers an alternative framework by integrating the principles of spirituality and technological ethics to maintain human dignity. This research contributes to the discourse of philosophy of technology by offering a critical dialog between Western and Islamic traditions in responding to the challenges of sexuality in the digital era. The implications include the need for a multidisciplinary approach that integrates technological ethics with transcendental values.